2021
DOI: 10.1111/opo.12802
|View full text |Cite
|
Sign up to set email alerts
|

The effect of scleral lenses on vision, refraction and aberrations in post‐LASIK ectasia, keratoconus and pellucid marginal degeneration

Abstract: Purpose: To quantify the effect of a single scleral lens design on visual acuity and ocular higher-order aberrations in eyes with post-LASIK ectasia, keratoconus and pellucid marginal degeneration (PMD) that could not achieve satisfactory vision with spectacles or soft contact lenses. Methods: Forty-six eyes of 28 participants fitted with diagnostic scleral lenses (KeraCare) were analysed, including 19, 15 and 12 eyes with post-LASIK ectasia, keratoconus and PMD, respectively. Corrected distance visual acuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The baseline findings confirm the presence of a significant amount of HOAs in keratoconic eyes, while the use of a SL produced a marked reduction in RMS‐HOAs, coma, spherical aberration, secondary astigmatism and trefoil. This is consistent with several previous reports 6,12,15,34,35 6 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The baseline findings confirm the presence of a significant amount of HOAs in keratoconic eyes, while the use of a SL produced a marked reduction in RMS‐HOAs, coma, spherical aberration, secondary astigmatism and trefoil. This is consistent with several previous reports 6,12,15,34,35 6 .…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have reported a substantial increase in coma and spherical aberrations due to the displaced cone 33 . In this study, RMS coma and RMS trefoil were significantly elevated, and this was in agreement with previous studies of keratoconic eyes 6,34 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…8,11,12,22,23 However, the reduction in HOAs is less significant in our study, with a 46% reduction compared with more than 60% for other studies. 8,[23][24][25][26] The lower improvement in HOAs could be because of several factors. The age of our patients could have an impact; the average was less than 35 years against 53.8 years for our study.…”
Section: Discussionmentioning
confidence: 99%
“…The age of our patients could have an impact; the average was less than 35 years against 53.8 years for our study. 8,[23][24][25][26] The type of refractive surgery may also explain the results; in our sample, some patients had refractive surgeries with old methods: PRK or radial keratotomy (20% of eyes), in contrast to the majority of other studies where patients had only LASIK. 8,[23][24][25] In addition, these patients had a lower baseline acuity than in the other studies.…”
Section: Discussionmentioning
confidence: 99%